Neutrophils releasing IL-17A into NETs are essential to plasma cell differentiation in inflamed tissue dependent on IL-1R. (17th February 2017) - Grund, Lidiane Zito; Novaski, Ivan; Quesniaux, Valerie F.; Ryffel, Bernhard; Lopes-Ferreira, Monica; Lima, Carla
Abstract: Interleukin (IL) 17A in chronic inflammation is also produced by innate immune cells as neutrophils. Mice with chronic humoral response induced by venom of Thalassophryne nattereri (V Tn ) proved to be a good tool for evaluating the impact of IL-17A on the development of long-lived plasma cells in the inflamed peritoneal cavity. Here, we report that V Tn induces IL-17A production by neutrophils accumulating in the peritoneal cavity and triggers the extrusion of IL-17A along with neutrophil extracellular traps (NETs). Neutrophil depletion reduced the number of IL17A-producing cells in V Tn -immunized mice and blocked the differentiation of long-lived plasma cells. Specific antibody production and survival of long-lived plasma cells was ablated in V Tn -immunized mice deficient in CD4, while CD28 signaling had the opposite effect on differentiation of long-lived plasma cells. Further, maturation of long-lived plasma cells in inflamed peritoneal cavity was IL-1R1 and COX-2 dependent. Finally, when both the Raf-MEK-ERK pathway and the IL-17A or IL-1R1 activities were blocked, neutrophils were unable to promote the differentiation of memory B cells into long-lived plasma cells, confirming the essential role of neutrophils and IL-17A along with NETs in an IL-1/IL-1R-dependent manner as the novel helping partner for plasma cell differentiation in chronically inflamed tissues.